Cost-effective power assessment in paralympic wheelchair athletes - Carlos Talayero; Ignacio López-Moranchel; Raúl Díaz-López; Olga López-Torres (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: power measurement in sports is essential to enhance performance, but technological and economic limitations hinder its application in Paralympic contexts.